2016
DOI: 10.1149/2.0771609jes
|View full text |Cite
|
Sign up to set email alerts
|

All-Solid-State Lithium-Sulfur Battery Based on a Nanoconfined LiBH4Electrolyte

Abstract: In this work we characterize all-solid-state lithium-sulfur batteries based on nano-confined LiBH 4 in mesoporous silica as solid electrolytes. The nano-confined LiBH 4 has fast ionic lithium conductivity at room temperature, 0.1 mScm −1 , negligible electronic conductivity and its cationic transport number (t + = 0.96), close to unity, demonstrates a purely cationic conductor. The electrolyte has an excellent stability against lithium metal. The behavior of the batteries is studied by cyclic voltammetry and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(120 citation statements)
references
References 69 publications
6
114
0
Order By: Relevance
“…After confining LiBH 4 into the ordered mesoporous silica, the phase transition temperature was reduced to 90 °C and the ionic conductivity at room temperature can reach up to 0.1 mS cm −1 . Further an ASS Li–S battery based on this confined LiBH 4 electrolytes were reported and exhibited very high sulfur utilization and good cycle stability (more 1200 mAh g −1 after 40 cycles at 0.03C) at a moderate temperature—55 °C …”
Section: Development Of Ass Li–s Batteriesmentioning
confidence: 97%
See 2 more Smart Citations
“…After confining LiBH 4 into the ordered mesoporous silica, the phase transition temperature was reduced to 90 °C and the ionic conductivity at room temperature can reach up to 0.1 mS cm −1 . Further an ASS Li–S battery based on this confined LiBH 4 electrolytes were reported and exhibited very high sulfur utilization and good cycle stability (more 1200 mAh g −1 after 40 cycles at 0.03C) at a moderate temperature—55 °C …”
Section: Development Of Ass Li–s Batteriesmentioning
confidence: 97%
“…The sulfide‐based electrolytes are the most promising SSEs for ASS Li–S batteries and were widely used to construct ASS batteries for the high ionic conductivity, good compatibility with sulfur and easy fabrication of cells and cathode, which has been elaborated in the above part . In the past years, most of the composite cathodes applied in ASS Li–S batteries were prepared by mechanically mixing SSEs, conductive additives and sulfur . According to the report from Tatsumisago and co‐workers, the different fabrication methods for cathode can impose a significant influence in battery performance .…”
Section: Development Of Ass Li–s Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the use of LiBH 4 , its P63/mmc phase is stable at temperatures above 110 °C so that it can deliver an ionic conductivity of ≈1 mS cm −1 at 120 °C . In this perspective, Das et al investigated the performance of all‐solid‐state Li–S batteries using LiBH 4 solid electrolyte. The cell composed by sulfur/carbon cathode and lithium foil anode could deliver a reversible capacity of about 1200 mA h g −1 at 0.03 C even at a temperature as high as 55 °C.…”
Section: Electrolytementioning
confidence: 99%
“…Recent interest in utilizing LiBH 4 as a solid-state electrolyte was established through the work of Orimo [4], who demonstrated that the ionic conductivity of lithium can be greater than 1 mS/cm at temperatures above the orthorhombic to hexagonal phase transition that occurs at 380 K [5]. This work has been expanded to achieve high conductivity in LiBH 4 based solid electrolytes through the addition of Li halide salts [6][7][8], nanoconfinement [9][10][11][12], nanoionic destabilization [13,14], ion substitution [15][16][17][18][19][20][21], and eutectic formation [22].…”
Section: Introductionmentioning
confidence: 99%